2018
DOI: 10.3390/nu10091136
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Choice in Weight Loss Strategies: A Systematic Review and Meta-Analysis

Abstract: Effective strategies to achieve weight loss and long-term weight loss maintenance have proved to be elusive. This systematic review and meta-analysis aims to explore whether the choice of weight loss strategy is associated with greater weight loss. An electronic search was conducted using the MEDLINE (Medical Literature Analysis and Retrieval System Online, or MEDLARS Online), EMBASE (Excerpta Medica database), CINAHL (Cumulative Index to Nursing and Allied Health Literature), and PsycINFO (Database of Abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In fact, three studies demonstrated a statistically significant increase in mean weight loss in participants in the no‐choice groups. Of note, attrition rates were similar in choice and no‐choice groups in the studies, indicating no particular advantage in offering a choice to weight‐loss participants regarding adherence and retention 80 …”
Section: Commercial Dietsmentioning
confidence: 89%
“…In fact, three studies demonstrated a statistically significant increase in mean weight loss in participants in the no‐choice groups. Of note, attrition rates were similar in choice and no‐choice groups in the studies, indicating no particular advantage in offering a choice to weight‐loss participants regarding adherence and retention 80 …”
Section: Commercial Dietsmentioning
confidence: 89%
“…18,19 4.4 | Evidence on the effect of being assigned to the preferred treatment on weight loss outcomes Weight loss studies that incorporate participants' preference to test the effect of preference on weight loss outcomes do not provide strong evidence that receiving a preferred treatment leads to or is associated with better outcomes compared with receiving a randomly assigned treatment or the non-preferred treatment. [20][21][22][23][24][25] For example, Renjilian et al 21 randomly assigned adult participants with obesity to the weight loss treatments for which they expressed preference within a 2  2 factorial design (individual/group treatment  preferred/non-preferred).…”
Section: Why It Is Important To Know Preference Proportionsmentioning
confidence: 99%
“… [13] Dietary patterns most associated with reduced CVD risk are those that: [ 6 , 7 , 8 , 9 , 10 ] • Prioritize: Vegetables, fruits, legumes, nuts, whole grains, seeds, and fish Foods rich in monounsaturated and polyunsaturated fatty acids such as fish, nuts, and non-tropical vegetable oils Soluble fiber •Limit: Saturated fat, such as tropical oils, as well as ultra-processed meats preserved by smoking, curing, or salting or addition of chemical preservatives, such as bacon, salami, sausages, hot dogs, or processed deli or luncheon meats, which in addition to containing saturated fats, may also have increased sodium, nitrate, and other components which might account for an increase CVD risk compared to unprocessed red meat [14] Excessive sodium Cholesterol, especially in patients at high risk for CVD with known increases in cholesterol blood levels with increased cholesterol intake Ultra-processed carbohydrates Sugar-sweetened beverages Alcoholic beverages [ 15 , 16 ] Trans fats
Figure 1 Adoption of healthful nutrition is a shared decision process between clinician and patient, with priorities based upon evidence-based dietary patterns, nutrition goals, cultural applicability, cost, and availability. While potentially counterintuive, patient preference is not consistently associated with improved health outcomes when implemeting medical nutrition therapy [17] , [18] , [19] . Healthful food choices made after medical nutrition therapy may differ from “preferred” food choices made before medical nutrition therapy.
…”
Section: Introductionmentioning
confidence: 99%
“… Adoption of healthful nutrition is a shared decision process between clinician and patient, with priorities based upon evidence-based dietary patterns, nutrition goals, cultural applicability, cost, and availability. While potentially counterintuive, patient preference is not consistently associated with improved health outcomes when implemeting medical nutrition therapy [17] , [18] , [19] . Healthful food choices made after medical nutrition therapy may differ from “preferred” food choices made before medical nutrition therapy.…”
Section: Introductionmentioning
confidence: 99%